PROFIL HUTAN MANGROVE TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Elva, Novia Monika; Eka Putri, Irma Leilani; Rizki, Rizki (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Profile of vegetation is the worldâs oldest methods determining the architecture of a forest canopy. Forest profile diagrams can also be used to portray the vertical structure (stratification) or horizontally from the forest. With the forest profile is also used to predict the condition of a trees of the future, trees of the present and trees of the past. The purpose of this study was to determine profile of mangrove forest and future predict environment in mangrove forest Teluk Buo Kecamatan Bungus Teluk Kabung Kota Padang. Methods used in this research is belt transect. The profile of this forest made by making transect perpendicular to the edge of the lagoon, mangrove vegetated areas cut off from the front to the back of the mangrove forest. On the belt transect made a plot continuously with size 10x10m, making the forest profile is made with the data in diameter. Profile Teluk Buo Kecamatan Bungus Teluk Kabung Kota Padang forest has one tree strata.Â